PELAKSANAAN PENGIKATAN JUAL BELI RUMAH MELALUI SISTEM PESAN BANGUN PADA PT. PRATAMA GRIYA MAKMUR KABUPATEN PASAMAN BARAT - Baldi Pramana; Busyra Azheri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The home marketing strategy that is currently being used is home sales in the form of images (pre-project selling). The transaction is set out in the form of Bonds for Sale and Purchase (PJB) which in practice raises various problems, both in terms of PJB content and the quality of work results. PJB for developers is often used to break the law and legislation such as by disguising the actions of company directors for and on behalf of themselves, consumers are required to pay excess land prices that were not previously agreed and thought of, down payments that originally increased from the price offered, the construction of the house is not in accordance with the specifications and general standards, the delay in the submission of the certificate, the fasum problem, which should be the responsibility of the developer. From the description above, the problem examined was how to implement the sale and purchase of houses through the built-in message system at PT. Pratama Griya Makmur Regency of West Pasaman and how to protect the rights of consumers. This study uses an empirical juridical approach. The results of the study show the implementation and legal protection for consumers in buying and selling houses through a built-in message system at PT. Pratama Griya Makmur, West Pasaman Regency has been carried out by breaking the rules, namely parties representing companies in making PJB are directors, acting for and on behalf of themselves, in PJB the building specifications are not included, sanctions for cancellation of agreements, rights and obligations of the parties are not included implicitly.